2014
DOI: 10.1007/s00405-014-3305-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 potentiates myelination and recovery after facial nerve injury

Abstract: Roles of vitamin D on the immune and nervous systems are increasingly recognized. Two previous studies demonstrated that ergocalciferol (vitamin D2) or cholecalciferol (vitamin D3) induced functional recovery and increased myelination in a rat model of peroneal nerve transection. The current report assessed whether cholecalciferol was efficient in repairing transected rabbit facial nerves. Animals were randomized into two groups of rabbits with an unilateral facial nerve surgery: the vitamin D group included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
3
23
0
2
Order By: Relevance
“…Our findings are similar to those from a study by Montava et al, in which facial nerve injury was induced in an experimental animal model. After 200 IU/kg/day oral vitamin D treatment, calcitriol induced functional recovery and myelination starting from the 6 th week, and myelination response was seen electrophysiologically starting from the 12 th week 7 . It has also been shown that in rat models with peroneal nerve injury, cholecalciferol and calcitriol induce peroneal nerve healing 8 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Our findings are similar to those from a study by Montava et al, in which facial nerve injury was induced in an experimental animal model. After 200 IU/kg/day oral vitamin D treatment, calcitriol induced functional recovery and myelination starting from the 6 th week, and myelination response was seen electrophysiologically starting from the 12 th week 7 . It has also been shown that in rat models with peroneal nerve injury, cholecalciferol and calcitriol induce peroneal nerve healing 8 .…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin D is a steroid molecule and it is synthesized from 7-dehydrocholesterol by the action of ultraviolet B rays in the epidermis 6 . Experimental animal model studies demonstrated that vitamin D increases myelination after peripheral nerve injury and reduces neuronal injury 7,8 . Vitamin D deficiency may cause hyperinnervation and hypersensitivity in the nerve fibers and increases pain sensation and pain perception in the pathological process 9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…CYP27A1, CYP2J2 and CYP3A4 are potential players for the addition of a hydroxyl group on C25 of vitamin D, but CYP2R1 appears to be the most implicated enzyme in the conversion of cholecalciferol into 25 hydroxyvitamin D3 (25OHD3), or calcidiol (Cheng et al, 2003;Schuster, 2011). 25 (Holick, 2007). Within the whole body, calcitriol binds to the vitamin D receptor (VDR) and induces the transcription of hundreds of genes."…”
Section: Reviewermentioning
confidence: 99%